Republic of the Marshall Islands : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
The 2018 Debt Sustainability Analysis (DSA) assesses that the Republic of the Marshall Islands (RMI) remains at high risk of debt distress. The ratios of the present value (PV) of external public and publicly-guaranteed (PPG) debt to GDP and to exports are currently just below their respective policy-dependent indicative thresholds. The PV of the PPG debt-to-GDP ratio is expected to decline slightly in the near term, but to start increasing and exceed its indicative threshold in the medium to long term. Stress tests confirm the vulnerability of the debt position to lending terms as well as macroeconomic shocks. Although the RMI does not currently face debt servicing risks, helped by government revenue from fishing licenses and a stable flow of funds from the U.S. Compact grants until FY2023, a lack of fiscal buffers after FY2023 and risks from contingent liabilities call for a fiscal reform strategy. Containing the risk of debt distress requires continuation of grants to support the country’s large development needs, and implementation of fiscal and structural reforms to promote fiscal sustainability and growth.